Crítica às “teorias” da liderança: da teoria política às prescrições - Castro, Breno Antonio Rodrigues de (2018)
This study is a theoretical essay, having as a methodology for the analysis of leadership the study of the so-called "schools" of leadership and political theory, subjecting the literature in analysis to the scientific method established by the philosophy of science. This dissertation defends the thesis that there is no theory of leadership in terms established by scientific epistemology, which are: a) the definition must be clearer than what is defined; b) the definition should, as far as possible, affirmatively define the reality to be defined; c) the definition should not go back to the term to be defined; d) it is necessary that the definition refers to the essence and not to the properties or characteristics; e) the concept can not be very extensive and low-key. As a consequence, what management literature calls a theory, in the light of the philosophy of science, is a set of prescriptions for the exercise of leadership in organizations. The arguments to support this thesis lie in the philosophy of science - which organizes the method from which it is thought to be a phenomenon - and in classical political theory. This dissertation aims to analyze two aspects arising from the above-mentioned thesis: 1) to analyze the prescriptions about leadership in the light of political theory and 2) to point out the fragility of these prescriptions. Thus, if leadership as described by management literature is not theory, we conclude that there is no theory of leadership (there are no definitions, arguments are just metaphors, isolated cases, common sense), no "school" fulfills the requirements for define leadership. Prescriptions are more sophisticated forms of control aimed at concealing the conflicts arising from the power relations inherent in organizations